1992
DOI: 10.2307/30148460
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus in U.S. Hospitals, 1975–1991

Abstract: OBJECTIVES: Analyze changes that have occurred among U.S. hospitals over a 17-year period, 1975 through 1991, in the percentage of Staphylococcus aureus resistant to b-lactam antibiotics and associated with nosocomial infections. DESIGN: Retrospective review. The percentage of methicillin-resistant S aureus (MRSA) was defined as the number of S aureus isolates resistant to either methicillin, oxacillin, or nafcillin divided by the total number of S aureus isolates for which methicillin, oxacillin, or nafcillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
100
0
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(111 citation statements)
references
References 33 publications
4
100
0
7
Order By: Relevance
“…And must also be able to make independent referral to other health care professionals." 3 The potential value of such a practitioner was recognised by recent reports from both the Clinical Standards Advisory Group and the Audit Commission. 4 5 Nurse practitioners in accident and emergency departments can reduce waiting times, improve staff morale, and facilitate the more sensible use of resources.…”
Section: Nurse Practitioners and Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…And must also be able to make independent referral to other health care professionals." 3 The potential value of such a practitioner was recognised by recent reports from both the Clinical Standards Advisory Group and the Audit Commission. 4 5 Nurse practitioners in accident and emergency departments can reduce waiting times, improve staff morale, and facilitate the more sensible use of resources.…”
Section: Nurse Practitioners and Primary Carementioning
confidence: 99%
“…Even in areas without apparent MRSA, speculative screening has detected positive patients, 4 questions-and may not succeed. 3 Even local treatment with topical antiseptics may have adverse effects and is unlikely to reduce carriage in sites such as the gut. 8 Carriage by staff shows that harbouring MRSA is compatible with continuing health.…”
Section: Eric Fowler/sismentioning
confidence: 99%
“…Nevertheless, there is room for improvement. Despite the stringent application of conventional infection control measures, there has been an inexorable increase in multiresistant Staphylococcus aureus in hospitals around the world 17 – 19. Clearly, novel strategies are required if we are not to repeat this with the newly emerged vancomycin resistant strains 20.…”
mentioning
confidence: 99%
“…In the present study, MRSA counted only for 4.6% of the total collected isolates and 89% of S. aureus isolates which probably indicated the need for better understanding to infection control measures in the hospitals. Prevalence of MRSA in hospitals increased from 2.1% in 1975 to 35% in 1991 [24] and it was 46% in Western Pacific region, 5.7% in Canada, varied from less than 2% in the Netherlands to 54.4% in Portugal, from 23.6% in Australia to more than 70% in Japan and Hong Kong [25] [26] and 30% -60% in Thailand [27]. For serious MRSA infections, vancomycin is the treatment of choice and MRSA strains with reduced susceptibility to vancomycin have been reported [28] [29] but in this study no vancomycin resistant isolates were found.…”
Section: Discussionmentioning
confidence: 99%